How to Use a Dichotomous Key: A Tutorial Featuring 10 Common Shade Trees of the Tampa Bay Area - Andrew K. Koeser; Gitta Hasing; Michael G. Andreu; Melissa H. Friedman (EDIS)
A dichotomous key is a tool used to help identify an unknown organism. This 12-page fact sheet features a key of leaf characteristics for ten common broadleaf trees in the Tampa Bay Area. Accurately navigating this series of paired, either-or choices about leaf characteristics will lead the reader to identify the correct tree from the group of ten. Written by Andrew K. Koeser, Gitta Hasing, Michael G. Andreu, and Melissa H. Friedman, and published by the Environmental Horticulture Department, June 2016.